Introduction: Toward an old understanding of philology: Exploring the literary construction of place as religious and social commentary in Asia - Hegarty, James Marcel Marcel (Acta Orientalia Vilnensia, 2007)
Cardiff UniversityThere is no doubt that the idea of place matters. Human beings have long been willing to fight and die for rights, symbolic and material, over both tangible and intangible places. However, the types of expression and performance that transmit and adapt ideas of place are less well understood than the brute fact of the enduring power of certain charged locations. That is to say, we know that certain places are significant but we are less sure as to the mechanisms of how and why they are made so. In addition, scholarly work in this area has tended to consider the literary and performative construction of place to always be bound up with these determinate locations rather than a variety of social functions. Literary engagements with the category of place, as this volume will demonstrate, encompass a wide range of uses. A suggestive but by no means exhaustive list of those that reflect the analytic content of this volume would have to include: political and religious legitimation, the construction of the significant past, the expression of agreement and dissent in relation to prevailing and emergent ideologies, and the transmission and adaptation of systems of socially significant knowledge in response to a wide variety of historical circumstances. Literatures of place, then, provide an extraordinarily rich source of information as to the ways in which human beings maintain and transform their understandings of not just the world around them, but themselves.